(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: There are various causes of hypochromic microcytic anaemia. Among these β-thalassemia trait and iron deficiency anaemia are much more common in developing country like India. Various parameters obtained on automated haematology analyser by calculating discriminant functions to differentiate iron deficiency anaemia and β thalassemia trait becomes easy and cost effective. Objective: To differentiate iron deficiency anaemia and β-thalassemia trait by blood indices, red cell distribution width and various discriminant functions. Materials and Methods: This study was carried out in the pathology department of AMC MET medical college, L.G.Hospital, Maninagar, Ahmedabad. We had studied 100 cases of differentiating Iron deficiency Anaemia and β-Thalassaemia trait from patient’s case records and laboratory reports irrespective of age and sex over a period of one year (January 2019 to December 2019). Tests for serum iron and ferritin were carried out in individuals showing low hemoglobin (Hb). All the selected subjects’ samples were subjected to blood morphology, comparison of MCV, RBC count, RDW, RDWI, SI, GI and MI. Results: Out of 100 cases seventy five were diagnosed having IDA, whereas twenty five were having β-TT. The RBC count was higher, and MCV was much lower in βTT as compared to IDA. Both groups were subjected to RDW,RDWI, SI, MI and GI. Conclusion: Among various discriminant function calculated from different haematological parameters and blood indices Mentzer index and Srivasta index are more sensitive and specific for differentiating IDA and β-TT.